Manusia Sebagai Individu, Keluarga, Masyarakat - Natasya Olivia Ningrum; Ferren Audy Febina Sitompul; Devi Ariani; Rahma Yani (IAI Nasional Laa Roiba Bogor, 2024)
Humans are creatures that have reason and thoughts that are able to influence other people for the sake of their survival. Humans are also social beings who in their survival need other people. Humans as individuals, as families and as societies have different concepts from one another. The individual has the meaning of a unitary entity which has a limit, meaning that as a human being an individual is not a human being who is comprehensive in nature, the family has the meaning of a small group that exists in the life of society in which it is formed by the agreement of two human beings while society is a broad group of people who are bound to a culture and are considered The same. In the context of humans as individual humans, they are creatures that are not divided. In this undivided relationship with the soul and body of the human itself, in the context of the human family, they are agents of biological formation, which previously had an agreement between two human beings. In the context of human society, it is an important element in it because in that society there are humans who make the establishment of a community association which is then able to give birth to the culture that they will carry out. Keywords: Human, Individual, Family, society.